AKIBAT HUKUM TERHADAP PERUBAHAN PERJANJIAN PERKAWINAN DALAM PERATURAN MENTERI AGAMA NOMOR 19 TAHUN 2018 - Hafis, Muhammad; Nelli, Jumni; Elmiati, Nia (Hukum Islam, 2022)
Marriage agreements are usually made before or at the time the marriage takes place. This agreement is known as a prenuptial agreement. As contained in Law Number 1 of 1974 Article 29, it is stated that at the time before the marriage took place, both parties with mutual consent can enter into a written agreement which is legalized by the marriage registrar, after which the contents also apply to third parties as long as the third party is involved. However, with the issuance of the Constitutional Court's decision no. 69/PUU-XIII/2015 regarding a material review of Article 29 of Law Number 1 of 1974 concerning Marriage, which was then followed by Regulation of the Minister of Religion of the Republic of Indonesia Number 19 of 2018 concerning Marriage Registration, which in the end said that it is not permissible to make A marriage agreement after The marriage takes place is contrary to the 1945/ inconstitutional law, so the author feels it is very necessary to conduct a study of the arguments of the Constitutional Court and what legal consequences arise from the change in the marriage agreement.In this paper the author uses the normative legal method, using an empirical juridical approach. The empirical juridical approach is an approach used in research by examining theories, concepts, legal principles and legislation related to research. The result of this study is that the decision of the Constitutional Court no. 69/PUU-XIII/2015 creates legal consequences for joint assets, results in the distribution of inheritance, as a result of causing legal uncertainty, and with this decision it can also lead to disharmony in the relationship between husband and wife in the future.